The Impact of Antibiotic Use in Breastfeeding Women on the Infant's Gut Microbiome—A Prospective Cohort Study. (4th October 2017) - Rock, Rachel; Ben-Amram, Hila; Neuman, Hadar; Hanya, Hodaya; Koren, Omry; Youngster, Ilan
Abstract: Background: The intestine of a newborn is considered sterile in utero and is rapidly populated with different bacteria following birth. The composition of the developing gut microbiome is thought to have crucial roles in maturation of the immune system and prevention of various diseases. Several factors can influence the development of the gut microbiome in early life, and much attention has been focused on the role of antibiotics in disrupting this delicate equilibrium. Up to 20% of women will require antimicrobial therapy during the first year post-partum. Though many antibiotics are considered safe during breastfeeding, it is well known that some degree of accumulation will occur in the breast milk. Little is known about the influence of maternal antibiotic consumption during breastfeeding on the infant's gut microbiome. Methods: A prospective study of breast-feeding mothers prescribed antibiotics, and their nursing infant. Breast milk and infant fecal samples were collected at six different time points before, during and after maternal antibiotic treatment. The glycobiome and gut microbiota were characterized by 16S ribosomal RNA gene sequencing. Antibiotic concentrations in breast milk were determined by HPLC. Demographic data and relevant medical information was obtained from participants. Results: 22 mother-infant pairs completed the study (mean age of infants 4 months, SD 2, 4). Antimicrobial consumption resulted in rapid reduction in alpha diversity in breast milk, with partial recovery by 30 days post antibiotic treatment. Infant gut microbiome showed distinct changes after maternal treatment which were mainly characterized by a decrease in the relative abundance of Bifidobacteria and Veillonella . Conclusion: Our preliminary study clearly showed a disruptive effect of maternal antibiotic consumption on the nursing infant's gut microbiome with an impact on the important early colonizers of the infant gut. Larger studies comparing the effect of different antibiotics on infant gut microbiome are needed, in addition to available safety data, to make informed recommendations about specific antibiotic use in breast-feeding women. Disclosures: All authors: No reported disclosures.